Electron beam dose dependence of surface recombination velocity and surface space charge in semiconductor nanowires. (17th May 2017) - Donatini, Fabrice; Sartel, Corinne; Sallet, Vincent; Pernot, Julien
Abstract: The characterization of nanowires (NWs) often requires the use of scanning electron beam techniques because of their high spatial resolution. However, the impact of the high energetic electron beam on the physical parameters under investigation is rarely taken into account. In this work, a combination of optical and electrical techniques is involved for the measurement of the electron beam dose (EBD) dependence of cathodoluminescence intensity, exciton diffusion length and electrical resistance in ZnO NWs. Large EBD dependences of these key parameters are observed and their reversibility is investigated. The results are discussed in terms of bulk and surface reversible modifications. In particular, the behaviors of surface recombination velocity and surface space charge under electron beam exposure are determined and simulated. This study points out that caution must be taken and experimental protocols must be well defined when measuring physical parameters of NWs using electron beam techniques.